Chloroplast protein import: solve the GTPase riddle for entry - Kessler, Félix; Schnell, Danny (My University, 2004)
The fidelity of the numerous intracellular protein-trafficking pathways to different organelles is dictated by the interactions between the intrinsic targeting signals of substrate proteins and specific receptors that deliver the substrate to the proper organelle. Recent studies of protein targeting to chloroplasts suggest a novel mechanism in which GTP-dependent substrate recognition is coupled to a GTP-driven motor that initiates the translocation of proteins into the organelle.
Keywords: OUTER ENVELOPE; PREPROTEIN RECEPTOR; TRANSIT PEPTIDE; TOC34; MEMBRANE; DOMAIN; ARABIDOPSIS; APPARATUS; ATTOC159; TOC159